2018
DOI: 10.18294/sc.2018.1342
|View full text |Cite
|
Sign up to set email alerts
|

Estudio exploratorio de validez y consistencia interna del índice de capacidad para el trabajo entre trabajadores de la salud

Abstract: El objetivo de este estudio fue evaluar la validez y la consistencia interna del índice de capacidad para el trabajo (ICT) entre trabajadores de la salud en Bahía, Brasil. Se trata de un estudio exploratorio de validez con base en un corte transversal de una muestra de 3.084 trabajadores de la salud. El análisis de componentes principales extrajo tres factores del instrumento con varianza total acumulada del 53,9%. A través del ICT se identificaron grupos de trabajadores por edad y se correlacionaron de forma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In other studies developed in Spain, Bascour-Sandoval et al [ 17 ] found a three-factor structure only previously seen in a Brazilian study [ 37 ]. The third factor was constituted only by subscale 7, “Mental resources”.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In other studies developed in Spain, Bascour-Sandoval et al [ 17 ] found a three-factor structure only previously seen in a Brazilian study [ 37 ]. The third factor was constituted only by subscale 7, “Mental resources”.…”
Section: Discussionmentioning
confidence: 84%
“…The international dissemination of the WAI has required its translation, adaptation to the particularities of each country's culture and professional practice and psychometric properties evaluation [ 5 ]. Consequently, this instrument has now been translated into a number of languages and validated in workers of different occupational categories from countries in Europe [ [6] , [7] , [8] ], Latin America [ [9] , [10] , [11] , [12] ], and Asia [ 13 ]. These studies have obtained different factorial structures of one, two, or even three factors.…”
Section: Introductionmentioning
confidence: 99%